Design Modification and Prototype Development of a Cross-Flow Turbine for a Low/Zero-Head Water Stream - Asim Ali; Muhammad Zohaib Azam; Muhammad Faiq; Ghulam Asghar (Engineering Proceedings, 2023)
Low/zero-head cross-flow turbines (LZH-CFT) possess vast potential in the field of renewable energy technology. This research presents a modified design of a cross-flow turbine specifically engineered to harness the untapped hydro-kinetic energy from low/zero-head water resources. Unlike traditional hydro turbines, the LZH-CFT leverages a cross-flow configuration to utilize the water flows of natural streams, making it an ideal solution for flow channels with low/zero head. The design is modified through ANSYS simulations by varying the rotor’s blade angles (from 0 to 90°) and 60° angle is found optimum. The prototype model of modified design is prepared and tested, which represents 62.5% RPM efficiency and provides double power as compared to the typical cross-flow turbine.